Gender dan GayaKepemimpinan Perempuan Di Jabatan Publik: Studi Fenomenologi Pelaksanaan Syariat Islam di Aceh - Rahma Hidayati; Nellis Mardhiah (Prodi Sosiologi FISIP Universitas Teuku Umar, 2018)
Acehnese women are known to be very unique, have distinctive moralist leadership styles and high fighting spirit with the nickname